2020
DOI: 10.1016/j.jhsa.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of 90 Macrodactyly Cases

Abstract: Purpose Macrodactyly is a rare, nonhereditary congenital deformity. Digital enlargement in macrodactyly involves all tissue types and presents alone or as part of a congenital deformity syndromes. Macrodactyly treatment largely depends on surgeons' experience and knowledge. Because there is a paucity of large cohort studies of macrodactyly in the literature, our goal was to retrospectively analyze macrodactyly cases in order to define a better system for diagnosis, classification, and prognosis.Methods Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 13 publications
2
27
0
3
Order By: Relevance
“…Although, none of our patients had a positive family history or any similar deformity consistent with other reports [ 7 , 17 ] and the external environmental factor did not seem to affect the pathogenesis of the pedal macrodactyly, multiple pregnancy and live birth accounted for 45%, indicating that intrauterine environment might play an important role in the pathogenesis of foot macrodactyly during fetal development [ 1 , 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…Although, none of our patients had a positive family history or any similar deformity consistent with other reports [ 7 , 17 ] and the external environmental factor did not seem to affect the pathogenesis of the pedal macrodactyly, multiple pregnancy and live birth accounted for 45%, indicating that intrauterine environment might play an important role in the pathogenesis of foot macrodactyly during fetal development [ 1 , 18 ].…”
Section: Discussionsupporting
confidence: 88%
“…The patient’s affected toes showed fast growth and continued to grow disproportionately, which is also known as the progressive type [ 1 , 2 , 5 ]. This case of macrodactyly was considered nonhereditary, consistent with the patient’s family history, as no family member had the same condition [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that macrodactyly predominantly occurs in males at a ratio of 1.2:1. Macrodactyly has a higher probability of affecting the second digits, with the progressive type having a higher proportion among all cases [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentro de las investigaciones más recientes se encuentran las de Hardwicke y et al en el 2012 con 32 casos 12 , y las de Wu y colaboradores con 90 casos de macrodactilia en China 13 , en donde la incidencia es mayor en varones 14 y con frecuencia afecta al dedo índice seguido por el dedo medio, así como también suele observarse un crecimiento progresivo hasta el cierre de las epífisis entre los 15 y 17 años 12 . Dentro de los reportes, se describe la presentación unilateral en el 95 % de los pacientes con macrodactilia 13 , función sensitiva preservada y movilidad que va disminuyendo con el paso de los años 15 . La macrodactilia puede ser una enfermedad aislada o estar asociada a sindactilia en el 10 % de los casos, y a la polidactilia y criptorquidia en un 2% 16 .…”
Section: Introductionunclassified